Influence of low-level supplementation with a high-protein feed on performance of beef cows grazing tallgrass-prairie range during the fall - Donald A. Llewellyn; R.C. Cochran; T.T. Martson; David M. Grieger; C.G. Farmer; T.A. Wickersham; D.D. Simms (Kansas Agricultural Experiment Station Research Reports, 2003)
An experiment was conducted to evaluate the effect of hand feeding a limited quantity of a high-protein supplement during the fall grazing period on cow and calf performance. The time of initiation of supplementation was also evaluated. One-hundred thirty-six multiparous, pregnant, spring-calving cows grazing native range were assigned to supplementation treatments. Control cows received no fall supplementation. Supplemented cows received 0.14% of body weight per day (1.5 lbs per day) of a high-protein supplement (40% crude protein, as-fed basis) approximately 2 months before and after weaning (Aug 15 to Dec 14; weaning = Oct 15) or only after weaning (Oct 15 to Dec 14). Supplement was fed 3 days per week (Monday, Wednesday, and Friday) and was prorated to deliver the designated daily amount. All cows received 4 lbs per day of the same supplement during the winter (Dec 14 until calving in early March). Fall and cumulative winter performance (body condition score and body weight) indicated that providing a limited amount of a high-protein supplement during the fall supplementation period can increase cow body condition and body weight, and in some cases, subsequent calf performance. Fall supplementation did not significantly affect the proportion of cows cycling prior to the breeding season or subsequent pregnancy rate.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; High protein feed; Tallgrass-prairie range